JENIS-JENIS ARACEAE DI KAWASAN CAGAR ALAM LEMBAH ANAI KABUPATEN TANAH DATAR SUMATERA BARAT - Ananda, Renta Dwi; M, Des; Rizki, Rizki (Pendidikan Biologi, 2013)
ABSTRACT Aracea is the latex herba that has spatha flower and spadik flower.  Generally, it lives wet area and most protect, there are some species of the plant live in dry area and exposed. Lembah anai preserve is some of nature conservation in West Sumatera. There is not researcher or reporter find out species of Aracea in Lembah anai preserve. The purpose of the research is to get information and description about species of Aracea   that find out in Lembah anai preserve regency Tanah Datar west Sumatera. This research starts in March until June 2013 by using direct survey method in the field, acquired data based on descriptive analysis. Based on this research got the result 34 species of Aracea that include 14 genus in lembah anai preserve kabupaten Tanah Datar west sumatera. The example of genus are Alocesia (1 spacies), Amydrium (1 species), Amorphophallus (1 species), Anadendrum (2 species ), Apobalis (1 species ), Arisaema (1 species), Caladium (2 species), Colocasia (1 species), Dieffenbanchia (1 species), Homalomena (2 species), Rhaphidophora (6 species), Schismatoglottis (4 species), Scindapsus (9 species) and Syngonium (1 species).